The use of the Bayesian approach in the formation of the student's competence in the ICT direction - Seisenbekova, Perizat; Shayakhmetova, Asem; Othman, Mohamed (IEEE, 2019)
The theory of Bayesian networks has recently become very popular in solving various applied problems in various areas of science and production. To effectively use the Bayesian approach, a high-quality software product is needed that implements the mathematical ideas of Bayesian networks in practice. Such software products currently developed quite a large number. This paper presents the most common ones. The paper gives a small introduction about the competence of students and explores the possibility of using Bayesian networks in the formation of the competence of an IT trainer. Developed an integrated algorithm for the formation of the competence of training in the direction of IT.